Spatial variation in nutrient dynamics among five different peatland types in the Alberta oil sands region. Issue 4 (6th August 2015) - Wood, Meagan E.; Macrae, Merrin L.; Strack, Maria; Price, Jonathan S.; Osko, Terrance J.; Petrone, Richard M.
Abstract: Wetlands are found extensively throughout the Western Boreal Plain, a region under pressure because of disturbance by the oil and gas industries. To understand how wetland systems may respond to disturbance and set targets for reclamation efforts, it is necessary to understand natural variability in nutrient dynamics in the landscape. The purpose of this study was to characterize spatial variability in peatland nutrient (nitrogen, N, and phosphorus, P) dynamics in the Athabasca Oil Sands (AOS) region. N and P availability and net mineralization rates in the upper 10 cm layer of peat were examined during the peak growing season in five peatlands that fell along an apparent moisture gradient. N and P dynamics within and among the sites were related to water table position, peat moisture content and temperature. Phosphorus supply rates and total inorganic N pools and supply rates were generally elevated under wetter conditions, whereas nitrate (NO3 − ) pools and supply rates and P pools did not vary along a moisture gradient. In general, net immobilization was observed at the wetter sites where nutrient pools were elevated and net mineralization was observed at drier sites where nutrient pools were lower. Nutrient transformation rates were most strongly driven by warmer temperatures. Nutrient availability and immobilization rates were anomalously high at one peatland (a disturbed fen with a semi‐permanent road and decommissioned well pads). We suggest that reclamation and management practices should focus on regulating peatland hydrologic conditions, optimizing these for the most desirable nutrient levels for vegetation growth. Copyright © 2015 John Wiley & Sons, Ltd.